Efektivitas Prenatal Yoga Dengan Teknik Birth Ball Pada Ibu Hamil Terhadap Nyeri Punggung - Ari Shanti, Elvika Fit; Utami, Nendhi Wahyunia (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: third-trimester pregnant women will experience discomfort such as increased shortness of breath, leg cramps, and back pain. Muscle imbalance around the pelvis that causes back pain. A method to treat the back pain is through prenatal yoga by using a birth ball which can increase blood circulation to the womb, as well as the ability of the pelvic muscles when the delivery time is incoming and can reduce back pain. Objectives: The purpose of this study is to analyze the effectiveness of prenatal yoga with Birth Ball Technique to pregnant women with back pain. Methods: Experimental design methodology with unpaired two-group difference test. The prerequisite test for the metrics uses the two-sample unpaired T-Test. The difference test used is the Mann-Whitney test. Results: The results of research using birth balls for pregnant women showed no back pain namely 6 pregnant women (42.8). pregnant women with moderate pain (28.5%), 3 mild pain pregnant women (21, 3%), and 1 pregnant woman with severe pain (7.1%). The results of the study without birth ball given show that most pregnant women fall into the moderate pain category as many as 6 respondents or 42.8%, the mild category is 4 respondents (28.5%), 2 pregnant women are in the painless category (14, 2%) and 2 respondents in the severe pain category (14.2%). Conclusions: The average result of the statistical test of the difference in the use of the birth ball with the sig value of 0.378> 0.05, it can be concluded that there is no difference in back pain in the birth ball technique group with the group with no birth ball.